1997
DOI: 10.1159/000218964
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine Plus Epirubicin in Untreated or Minimal Pretreated Patients with Chronic Lymphocytic Leukemia – Preliminary Results of a Phase-ll Study

Abstract: Background: Fludarabine has been reported to be the most effective single agent in previously treated chronic lymphocytic leukemia (CLL). Based on in vitro synergism of fludarabine with anthracyclines and on results showing a higher efficacy of CHOP against COP it seems to be advisable to try a combination of fludarabine and an anthracycline to improve response rates as well as long-term results. Aim of the multicenter study was to evaluate the rate and duration of remissions and to examine toxicity and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…21 Previous studies revealed that the response rate was not lower when 2-CdA or FAMP were combined with either cyclophosphamide, 14,31-33 mitoxantrone 17,34 or anthracycline. 35 Minimal residual disease (MRD) was evaluated by twocolor immunophenotyping in the patients who fulfilled morphological criteria for CR. MRD was identified in seven out of 18 patients (38.9%).…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous studies revealed that the response rate was not lower when 2-CdA or FAMP were combined with either cyclophosphamide, 14,31-33 mitoxantrone 17,34 or anthracycline. 35 Minimal residual disease (MRD) was evaluated by twocolor immunophenotyping in the patients who fulfilled morphological criteria for CR. MRD was identified in seven out of 18 patients (38.9%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy and toxicity of these combinations should be carefully evaluated in prospective randomized trials. 214,307,310 (74) 88 (35) 69 (10) 65 (9) Weiss et al …”
Section: Combinations Of Purine Analogues and Other Drugsmentioning
confidence: 99%